Discretion, Rules, and Law: Child Custody and the UMDA's Best-Interest Standard - Schneider, Carl E. (1991)
One barrier facing any attempt to devise a uniform law for diverse jurisdictions is the occasional - perhaps even frequent - difficulty of writing rules that will accurately guide judges. The law's ordinary solution to that difficulty is to give judges some measure of discretion. This article inquires into the nature and legitimacy of that technique. It does so by analyzing a particularly controversial provision of the Uniform Marriage and Divorce Act (UMDA). Section 402 of that Act states: The court shall determine custody in accordance with the best interest of the child. It then instructs the court to consider all relevant factors, including the parents' wishes, the child's wishes, the child's relationships with the significant people in his life, the child's adjustment to his home, school, and community, and the mental and physical health of all individuals involved